Rheological properties of radiation modified thermoplastic styrene elastomers - Żuchowska, D.; Meissner, W.; Steller, R. (Polimery, 2022)
The results of rheological investigations of triblock copolymers styrene/butadiene/styrene (SBS) and styrene/ethylene-co-butylene/styrene (SEBS), i.e. steady shear viscosity (eta), storage modulus (G’) and loss factor (tgdelta) measured at temp. 200 degreesC before and after electron beam irradiation (dose 0, 60 and 100 kGy) were presented. Irradiated and non-irradiated samples were also investigated before and after thermal treatment (60 min at 200 degreesC) in rheometer without shearing. On the basis viscosity, elastic modulus and loss factor changes (Table 1, Figs. 1-7) it has been stated that SBS copolymer is more susceptible to radiation and thermal treatments than SEBS. Both treatments lead to decrease in flowability of SBS and SEBS copolymers with simultaneous increase in their elastic properties. Results of 11, G’ and tgdelta measurements were also used for the interpretation of probable molecular structure changes caused by radiation and thermal treatments.